2018
DOI: 10.1109/tsp.2017.2788416
|View full text |Cite
|
Sign up to set email alerts
|

Performance Bounds for Finite Moving Average Tests in Transient Change Detection

Abstract: Due to the widespread deployment of Global Navigation Satellite Systems (GNSSs) for critical road or urban applications, one of the major challenges to be solved is the provision of integrity to terrestrial environments, so that GNSS may be safety used in these applications. To do so, the integrity of the received GNSS signal must be analyzed in order to detect some local effect disturbing the received signal. This is desirable because the presence of some local effect may cause large position errors, and henc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Moreover, the position and rotation angle tracking accuracies are significantly reduced when the LOS link is blocked [43], [55]. So, the LOS link is used for tracking position and rotation angle and either LOS detection methods or online blockage identification approaches can be adopted depending on the applications 17 [57]- [61]. This allows to simply switch to the BS that is in the LOS thanks to the ultra dense networks.…”
Section: B Conversion To Position and Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the position and rotation angle tracking accuracies are significantly reduced when the LOS link is blocked [43], [55]. So, the LOS link is used for tracking position and rotation angle and either LOS detection methods or online blockage identification approaches can be adopted depending on the applications 17 [57]- [61]. This allows to simply switch to the BS that is in the LOS thanks to the ultra dense networks.…”
Section: B Conversion To Position and Orientationmentioning
confidence: 99%
“…As an example, blockage can be modeled based on 2-D knife edge diffraction[56]. This allows the receiver to apply a transient change detection algorithm based on the mean change of a complex Gaussian distribution as the signal integrity metric for the LOS blockage identification[57].September 18, 2018 DRAFT…”
mentioning
confidence: 99%
“…Features for multipath classification were also extracted from the correlation sequences in [18]. Authors in [28] used the code discriminator output and the mean and variance of the slope of the correlation curve to monitor the signal quality. In a more recent paper [29], the authors reported the indoor LOS/MP signal classification performance using a deep leaning approach based on the tracking outputs of a pseudolite signal.…”
Section: Introductionmentioning
confidence: 99%
“…A type of detection problem closely related to anomaly detection is transient detection [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In many signal processing applications, it is of interest to detect short-duration statistical changes in observed data.…”
Section: Introductionmentioning
confidence: 99%